Targeting the tumour microenvironment in platinum-resistant ovarian cancer. (December 2021) - Cummings, M.; Freer, C.; Orsi, N.M.
Abstract: Ovarian cancer typically presents at an advanced stage, and although the majority of cases initially respond well to platinum-based therapies, chemoresistance almost always occurs leading to a poor long-term prognosis. While various cellular autonomous mechanisms contribute to intrinsic or acquired platinum resistance, the tumour microenvironment (TME) plays a central role in resistance to therapy and disease progression by providing cancer stem cell niches, promoting tumour cell metabolic reprogramming, reducing chemotherapy drug perfusion and promoting an immunosuppressive environment. As such, the TME is an attractive therapeutic target which has been the focus of intense research in recent years. This review provides an overview of the unique ovarian cancer TME and its role in disease progression and therapy resistance, highlighting some of the latest preclinical and clinical data on TME-targeted therapies. In particular, it focuses on strategies targeting cancer-associated fibroblasts, tumour-associated macrophages, cancer stem cells and cancer cell metabolic vulnerabilities.